Gene and Germline Editing in Maternal and Reproductive Health: A Narrative Review of Ethical Dilemmas and Scientific Advances - Donel Suhaimi; Sofyan Andri; Anastasya Hutapea; Sandi Arihta (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2026)
Introduction: In Utero Genetic Editing (IUGE) is an emerging technology intended to modify the fetal genome to prevent or treat genetic disorders before birth. While it presents significant medical potential, it raises complex ethical, legal, and regulatory challenges. Current interventions remain largely animal-based, with human applications at theoretical or preclinical stages.Methods: This review examines ethical guidelines, legal frameworks, and regulatory perspectives globally and in Indonesia. Sources included WHO, the Indonesian Obstetrics and Gynecology Association (POGI), Indonesian health laws, and journals such as the American Journal of Obstetrics and Gynecology (AJOG). Literature was drawn from PubMed, WHO databases, Indonesian archives, and AJOG publications (2015–2025).Results: WHO emphasized precaution and transparency, while POGI stressed maternal–fetal safety under strict oversight. Indonesia lacks specific regulation, requiring interventions to respect safety and human dignity. The United States and European Union maintain restrictive regulations, including embryo research bans.Conclusion: IUGE is promising for reproductive health but remains ethically and legally unresolved, requiring clearer frameworks before clinical translation. AbstrakPendahuluan: In Utero Genetic Editing (IUGE) merupakan teknologi baru untuk memodifikasi genom janin guna mencegah atau mengobati kelainan genetik sejak sebelum lahir. Teknologi ini menjanjikan manfaat medis, namun menimbulkan tantangan etik, hukum, dan regulasi. Hingga kini, sebagian besar intervensi masih berbasis penelitian hewan, sementara aplikasi pada manusia berada pada tahap teoritis atau pra-klinis.Metode: Kajian ini menelaah pedoman etik, kerangka hukum, dan regulasi dari perspektif global dan Indonesia. Sumber mencakup WHO, Perkumpulan Obstetri dan Ginekologi Indonesia (POGI), peraturan kesehatan nasional, serta jurnal internasional seperti American Journal of Obstetrics and Gynecology (AJOG). Literatur diperoleh dari PubMed, basis data WHO, arsip hukum Indonesia, dan publikasi AJOG (2015–2025).Hasil: WHO menekankan prinsip kehati-hatian dan transparansi, sementara POGI menegaskan keselamatan ibu–janin dengan pengawasan ketat. Indonesia belum memiliki regulasi khusus, tetapi mensyaratkan intervensi genetik menjaga keselamatan dan martabat manusia. Negara seperti Amerika Serikat dan Uni Eropa menetapkan aturan restriktif, termasuk larangan riset embrio.Kesimpulan: IUGE berpotensi meningkatkan kesehatan reproduksi, namun memerlukan regulasi yang lebih jelas sebelum penerapan klinis.Kata kunci: In Utero Genetic Editing, etika, regulasi, terapi janin, bioetika